E-LEARNING RESOURCES IN DISTANCE EDUCATION - Kadyrova Dilshodakhan Abdunabiyevna; Bakhromov Mansur (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The formation and development of the system of information provision of education by our government, the reform of the system of educational institutions according to the requirements of the "National Personnel Training Program", the creation and introduction of relevant state educational standards in this regard, the involvement of scientists and highly qualified specialists in providing educational institutions with the necessary textbooks and literature a number of things are being done, such as training and improving the qualifications of pedagogues in leading educational institutions in developed countries.